Analyzing the Use of English for Tactical Communication Between Coaches and Athletes: A Mixed-Methods Investigation in Competitive Sports Environments - Elisa Haddina; Arsi Zahiri; Faldin Sejahtera Halawa; Robert Parulian Marko Bancin; S. Ahmad Habibi; Muhammad Naufal Ramadhan; Deddy Putrawan Laia (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: Effective communication between coaches and athletes constitutes a critical determinant of competitive success in modern sports. English has emerged as the lingua franca of international athletics, yet the specific linguistic features and communicative patterns employed during tactical exchanges remain underexplored. This study investigates how English is utilized for tactical communication in multilingual sports settings and examines the relationship between communication clarity and athletic performance outcomes. The primary objective was to analyze the linguistic characteristics, frequency patterns, and effectiveness of English-language tactical communications between coaches and athletes in competitive environments, with particular emphasis on identifying communication factors that correlate with successful performance outcomes. Methods: A mixed-methods approach was employed with 156 participants (78 coach-athlete dyads) from 12 different sports disciplines across 8 countries. Data collection involved video analysis of training sessions and competitions (n=234 hours), linguistic corpus analysis of 3,847 tactical communication instances, semi-structured interviews (n=45), and performance outcome measurements. Statistical analyses included Pearson correlation, multiple regression, and ANOVA procedures using SPSS version 28.0. Results: Analysis revealed five primary tactical communication categories: strategic instructions (42.3%), motivational directives (23.7%), technical corrections (18.9%), situational awareness cues (10.4%), and emotional regulation statements (4.7%). Significant positive correlations were identified between communication clarity scores and performance metrics (r = 0.67, p < 0.001). Simplified syntax (mean length utterance = 6.8 words) and sport-specific terminology density (32.4%) characterized effective tactical communications. Native English proficiency showed minimal correlation with communication effectiveness (r = 0.18, p = 0.062), suggesting that functional English competency suffices for tactical contexts. Conclusion: English functions effectively as a tactical communication medium in international sports contexts through simplified linguistic structures, high-frequency sport-specific lexicon, and contextually embedded meaning-making. The study demonstrates that communication effectiveness depends less on grammatical accuracy than on clarity, brevity, and shared understanding of sport-specific terminology. These findings have implications for coach education programs and multilingual athlete development protocols.